Biocompatible Bacterial Cellulose-Poly(2-hydroxyethyl methacrylate) Nanocomposite Films. (5th September 2013) - Figueiredo, Andrea G. P. R.; Figueiredo, Ana R. P.; Alonso-Varona, Ana; Fernandes, Susana C. M.; Palomares, Teodoro; Rubio-Azpeitia, Eva; Barros-Timmons, Ana; Silvestre, Armando J. D.; Pascoal Neto, Carlos; Freire, Carmen S. R.
Abstract : A series of bacterial cellulose-poly(2-hydroxyethyl methacrylate) nanocomposite films was prepared by in situ radical polymerization of 2-hydroxyethyl methacrylate (HEMA), using variable amounts of poly(ethylene glycol) diacrylate (PEGDA) as cross-linker. Thin films were obtained, and their physical, chemical, thermal, and mechanical properties were evaluated. The films showed improved translucency compared to BC and enhanced thermal stability and mechanical performance when compared to poly(2-hydroxyethyl methacrylate) (PHEMA). Finally, BC/PHEMA nanocomposites proved to be nontoxic to human adipose-derived mesenchymal stem cells (ADSCs) and thus are pointed as potential dry dressings for biomedical applications.